Hidradenitis suppurativa is associated with hypothyroidism and hyperthyroidism: a large‐scale population‐based study. (25th November 2020) - Sherman, Shany; Tzur Bitan, Dana; Kridin, Khalaf; Pavlovsky, Lev; Hodak, Emmilia; Cohen, Arnon D.
Abstract: Background: Hidradenitis suppurativa (HS) is a chronic inflammatory disease involving the skin bearing apocrine glands. There are numerous comorbidities and associated diseases among patients with HS. The association of HS and thyroid abnormalities is equivocal. We aimed to explore whether HS is associated with thyroid disorders. Methods: In this cross‐sectional large‐scale population‐based study in Israel, patients with a validated diagnosis of HS were matched at a proportion of 1:5 with age‐ and gender‐matched healthy controls without HS. A cross‐checking for HS diagnosis by International Classification of Diseases, ninth revision (ICD‐9) coding, and hyperthyroidism and hypothyroidism by ICD‐9 coding was performed. Demographic and exposure covariates were identified. Univariate and multivariate logistic regressions were utilized to establish the association of HS with thyroid disorders. Results: Study participants included 4, 191 HS patients and 20, 941 controls. The average age of patients was 39.7 years old, and 61.8% were female. 53.4% of HS patients and 13.5% of controls ( P < 0.001) were smokers. Odds ratios (ORs) for hypothyroidism and hyperthyroidism in HS were 2.91 (95% confidence interval [CI] 2.48–3.40) and 2.25 (95% CI 1.55–3.28), respectively ( P < 0.001 for both). While the association of HS with hypothyroidism was maintained across genders and all age groups, and remained positive after controlling for smoking status, the association with hyperthyroidism remained positive only among females, middle‐aged patients, and nonsmokers. Conclusion: HS is independently associated with hypothyroidism. The association of HS with hyperthyroidism held significance only in limited subgroups. Smoking status is a major modifier, mainly in the association of HS with hyperthyroidism.